Information System Ordering Online Restaurant Menu At Hover Cafe - Kurniawan, Rano; Sutawan, Ahmad; Amalia, Rizky (APTISI Transactions on Management (ATM), 2020)
The rapid development of technology requires every business person to upgrade his technology to more sophisticated. Many business people have upgraded their systems to be computerized and even online, one of the business people is in the culinary field. The culinary field which is meant for example is the cafe One thing that can support the quality of ordering in a cafe is the ordering process. In the hover cafe the menu ordering system is still conventional, using a menu book. This of course can be a problem because the menu book used can be damaged or lost so that it can slow down the ordering process, not to mention if the customer requests additional orders, the waiter must come to the customer's table to record additional orders again. The method used in this research is the method of data collection, the method of observation, the method of interviewing, and the method of literature study conducted to obtain accurate data. Then the data are analyzed with SWOT to find out the company's weaknesses and strengths. In describing the flow of the system using UML (Unified Modeling Language) and PHP (Hypertext Preprocessor) as a programming language with a MySQL database as a database. Therefore we need a ordering media that utilizes information technology as a medium for selecting food and beverage (E-Menu) which can provide information about order menu details to facilitate customers in making and ordering food or beverage menus.